Optimasi Konsentrasi Retarder Lignosulfonate terhadap Thickening Time dan Compressive Strength pada Sistem Lightweight Cement Sumur Gas Dangkal - Hirzi Ashka Mazzaya; Felita Tsany Pandya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Shallow gas well cementing risks gas migration and lost circulation due to low fracture gradients. This laboratory study analyzes Lignosulfonate retarder concentration effects on the thickening time and compressive strength of a 11.67 ppg Class G-Hollow Glass Spheres (HGS) slurry. Dynamic testing utilized an HPHT Consistometer (BHCT 142°F, 2,845 psi), and static testing used an Ultrasonic Cement Analyzer (BHST 169°F) for 24 hours. Results established Formula C (0.14 GPS) as the optimum formulation, recording a thickening time of 4 hours 4 minutes 30 seconds, within the safe 4.0–4.5 hour pumping window. Formula C yielded a 24-hour compressive strength of 2,525 psi, exceeding the ≥ 2,000 psi field target while safely fitting the 10.50–12.50 ppg slurry window. Furthermore, the slurry demonstrated responsive hydration by reaching an initial strength of 500 psi within 6 hours 12 minutes, effectively improving zonal isolation and mitigating shallow gas migration risks.